Clinical utility of entecavir for chronic hepatitis B in Chinese patients - Wang JY (Dove Medical Press, 2013)
Jiyao WangZhongshan Hospital, Fudan University, Shanghai, Key Laboratory of Medical Molecular Virology of MOE/MOH, Shanghai, People’s Republic of ChinaAbstract: The People’s Republic of China has one of the highest rates of hepatitis B virus (HBV) infection. This review summarizes recent data from studies of entecavir, one of the recommended first-line oral therapies for treating chronic hepatitis B, in Chinese HBV-infected patients. Long-term treatment with entecavir is efficacious and well tolerated, and studies comparing entecavir with other nucleos(t)ide therapies, such as lamivudine, adefovir, and telbivudine, demonstrate superior antiviral effects for entecavir therapy and comparable safety profiles. Entecavir monotherapy and combination treatment with other nucleos(t)ide analogs has been shown to be efficacious in the treatment of lamivudine-resistant and adefovir-resistant patients with HBV infection, as well as in patients with multidrug-resistant disease. Entecavir has also been shown to be effective in patients with HBV-associated clinical morbidity, including cirrhosis and liver failure, as well as in preventing recurrence of HBV following liver transplantation and in preventing reactivation of HBV after immunosuppressive therapy. Although the cost of anti-HBV therapy is a particular concern in the People’s Republic of China, a number of studies have recently demonstrated that entecavir (particularly long-term therapy) represents a more cost-effective treatment strategy compared with other nucleos(t)ide therapies. Further research is required to assess the effects of entecavir combination therapy on hepatitis B surface antigen clearance, and in drug-resistant patients in the People’s Republic of China.Keywords: hepatitis B, entecavir, People’s Republic of China, nucleos(t)ides